Model Analisis IS-LM dalam Perspektif Islam - Melani Azzahra Nur; Maryam Batubara (Jurnal Penelitian Ekonomi Akuntansi, 2023)
Economic growth that exists today has always been a central issue in the problem of economic development. Economic development always aims to create prosperity in society in terms of increasing income, unemployment, and poverty. With that, the government can overcome it by enacting several forms of policies that have been created, namely fiscal policy and monetary policy. Therefore, fiscal policy and monetary policy will always be influenced by the goods market as well as the money market. In macroeconomic theory, the case of the goods market is depicted as the IS curve, while in the money extinguisher, it is described as the LM curve. The good market in the macroeconomic sphere will describe economic conditions in a position where the demand and supply of goods and services. Macroeconomic stability is seen from the equilibrium point between demand and supply in the process of producing goods and services in the market. The IS curve is a curve that shows a combination of interest rates and income levels consistent with equilibrium points in the market. The money market is a meeting in a market to generate short-term demand and supply of funds. This short-term fund is a fund collected from a company or individually with a certain amount of time limit in one year, which can be traded in the money market. Equilibrium will occur in the money market if there is a similarity between the supply and demand of money.